Pengaruh Budaya Organisasi Dan Kepemimpinan Terhadap Pengelolaan Tim Serta Peningkatan Pelayanan Faron Fotocopy Lamongan - Ganda Wahyu Saputri; Moh. Ariyanto; Shinta Bella Puspita; Prima Mufakhoma; Silfiana (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2025)
This study examines the role of organizational culture and leadership in team management and customer service at Faron Fotocopy. A qualitative descriptive approach was used to explore daily work dynamics within the organization. Findings reveal that a work culture emphasizing cooperation, open communication, and customer orientation significantly enhances service quality. Leadership that is firm yet adaptive also contributes to team effectiveness, especially when dealing with dynamic operational situations. The combination of these elements creates a supportive work environment, improves customer experience, and strengthens the business’s competitive advantage within the printing service industry.